Emerging role of gefitinib in the treatment of non-small-cell lung cancer (NSCLC) - M Tiseo; M Bartolotti; F Gelsomino; et al (Dove Medical Press, 2010)
M Tiseo, M Bartolotti, F Gelsomino, P BordiMedical Oncology Unit, University Hospital of Parma, Parma, ItalyAbstract: Most patients with non-small-cell lung cancer (NSCLC) present with advanced disease and their long-term prognosis remains poor. Epidermal growth factor receptor (EGFR)-targeted therapies, such as gefitinib, have been subjected to comprehensive clinical development. Several phase II and III trials evaluated the clinical efficacy of gefitinib as monotherapy in pretreated patients with advanced NSCLC, as well as both monotherapy and combined with chemotherapy in chemotherapy-naive patients. A phase III trial (ISEL) in heavily pretreated advanced NSCLC patients demonstrated some improvement in survival with gefitinib compared with placebo; however, the difference was not statistically significant within the overall population. A large phase III trial in pretreated patients (INTEREST) demonstrated the non-inferiority of gefitinib in comparison with docetaxel for overall survival, together with an improved quality of life and tolerability profiles. In a large phase III trial (IPASS) in Asian chemotherapy-naive, never or former light-smoker patients with adenocarcinoma, gefitinib was more effective than carboplatin–paclitaxel in prolonging progression-free survival, particularly in patients harboring EGFR gene mutations. Gefitinib was a generally well tolerated treatment, with skin rash and diarrhea being the most common treatment adverse events. As a result, gefitinib is expected to have a large impact on the management of patients with advanced NSCLC, in particular in EGFR mutated patients.Keywords: non-small-cell lung cancer, gefitinib, EGFR